2000
DOI: 10.1074/jbc.m005728200
|View full text |Cite
|
Sign up to set email alerts
|

The Relaxin Receptor-binding Site Geometry Suggests a Novel Gripping Mode of Interaction

Abstract: Relaxin has a unique, clearly identifiable, mixed function receptor-binding region comprising amino acid residues that evolve sequentially from the central portion of the B chain ␣-helix. Two arginine residues in positions B13 and B17 that project like forefinger and middle finger from the helix provide the electrostatic element opposed by the hydrophobic (thumb) element isoleucine (B20), offset from the arginines by about 40°. The binding intensity of relaxin to its receptor decreases by 3 orders of magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
83
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 24 publications
5
83
0
1
Order By: Relevance
“…However, an Ile 19 to Glu (the corresponding residue at the B-chain of INSL6 (40)) change not only abolished the activity of relaxin-3 for LGR7 but also decreased relaxin-3 activity for GPCR135 and GPCR142 dramatically, suggesting that INSL6 might not be a ligand for GPCR135, GPCR142, or LGR7. These results further support the proposition that R 12 EFIR 16 AVI 19 is serving as the RXXXRXXI motif for LGR7 binding (34).…”
Section: Discussionsupporting
confidence: 79%
“…However, an Ile 19 to Glu (the corresponding residue at the B-chain of INSL6 (40)) change not only abolished the activity of relaxin-3 for LGR7 but also decreased relaxin-3 activity for GPCR135 and GPCR142 dramatically, suggesting that INSL6 might not be a ligand for GPCR135, GPCR142, or LGR7. These results further support the proposition that R 12 EFIR 16 AVI 19 is serving as the RXXXRXXI motif for LGR7 binding (34).…”
Section: Discussionsupporting
confidence: 79%
“…The answer is that the native B-chain structure is fully retained, which allows for several conclusions to be drawn regarding the receptor interactions. It has been established that the primary binding site of relaxin for LGR7 is located within the R-X-X-X-R-X-X-I motif that is presented on one face of the B-chain helix (24), and recent mutational explorations of the relaxin-3 B-chain have shown that the same motif is crucial for the binding of relaxin-3 to both GPCR135 and LGR7 (21). The observation that the B-chain structure, including the receptor binding motif, is retained in the chimera thus provides a clear explanation for the high affinity binding to the GPCR135 and GPCR142 receptors, and is consistent with the idea of the B-chain alone carrying all structural features needed for activation of these receptors.…”
Section: Description Of the Structure And Comparison To Native Relaximentioning
confidence: 99%
“…From these structures together with the crystal structure of relaxin-2 and extensive structure-activity studies, a picture of the complex events involved in the recognition of a relaxin by its receptor is starting to emerge. A conserved binding motif Arg-X-X-X-Arg-X-X-Ile has been identified as a crucial interaction point for relaxin binding to LGR7 (24), and a similar motif (His-X-X-X-Arg-X-X-Val) is used by INSL3 for binding to its receptor (23). However, it is clear that several additional interactions are needed both for strong binding and subsequent activation of the receptors.…”
mentioning
confidence: 99%
“…Further processing of the connecting peptide results in the native 6 kDa RLX molecule found in circulation (O'Byrne et al 1989). The amino acid motif Arg-X-X-X-Arg-X-X-Ile, located in the middle of the B chain, is required for RLX bioactivity (Bullesbach & Schwabe 2000).…”
Section: Introductionmentioning
confidence: 99%